Digital Citizenship among Umm Al-Qura University Students during Corona Pandemic - Alqarni, Ali; Alabdulkareem, Maha (Journal of Umm Al-Qura University for Educational and Psychological Sciences, 2023)
The study sought to ascertain the extent to which digital citizenship has been evident among Umm Al-Qura university students before and after the Coronavirus pandemic. It substantiated statistically significant differences based on three variables: gender, level of education, major, and academic year. The study collected data via a questionnaire from a sample of 433 Saudi university students recruited during the academic year 22021/2022. The data were analyzed using statistical measures, categorized and interpreted. Results of the descriptive statistics (means and standard deviations), correlational coefficients, ANOVA and t-test, were used in analyzing the data. Results showed that digital citizenship was generally patent before and after the Corona pandemic, with some statistical differences in favor of the post-pandemic. After the pandemic, results revealed statistically significant differences relevant to the gender variable, academic level and major. The differences were in favor of the males, the graduate students, and the applied majors. No statistically significant differences pertained to the variable of the academic year. Before the pandemic, no differences pertained to gender, major, and academic year variables. However, some differences existed concerning the academic level in favor of higher studies students. Based on results and discussions, important recommendations are provided.